2011
DOI: 10.1299/jtst.6.268
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Emission Spectra of Flames in Combustion Chamber of Swirling-Oxidizer-Flow-Type Hybrid Rocket Engines

Abstract: In order to clarify flame behavior in the combustion chamber of swirling-oxidizer-flow-type hybrid rocket engines, a small hybrid rocket engine with a large quartz glass window was fabricated to observe the inside of the combustion chamber from the front directly. PP and PMMA fuel grains were burned under the swirling and non-swirling oxygen flow conditions. For both PP and PMMA combustion, the disturbed swirling flames were found to develop closer to the grain surface than those without swirl, resulting in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The flame confirmed by the experiment that Professor Yuasa and others used PP and PMMA for was not observed. [7] Also the gaseous material observed in combustion chamber was similar to filament-like structures which were reported by Ashley A. Chandler in Stanford University. [8] Figure8 shows the pictures of digital single-lens reflex camera.…”
Section: A Results Of Visualization and Comparison With Different Posupporting
confidence: 69%
See 2 more Smart Citations
“…The flame confirmed by the experiment that Professor Yuasa and others used PP and PMMA for was not observed. [7] Also the gaseous material observed in combustion chamber was similar to filament-like structures which were reported by Ashley A. Chandler in Stanford University. [8] Figure8 shows the pictures of digital single-lens reflex camera.…”
Section: A Results Of Visualization and Comparison With Different Posupporting
confidence: 69%
“…These methods were established by Prof. Yuasa at Tokyo Metropolitan University. [7] This mechanism enables to observe flame directly. Figures 3 shows the schematic diagram of each fuel grain shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], the relationship between regression rate and maximum specific impulse was studied. According to the authors, since the regression rates are lower in hybrid propulsion, it is much more difficult to achieve the maximum theoretical specific impulse in the richest region of the fuel surface.…”
Section: Andmentioning
confidence: 99%
“…Here we have treated precisely those effects that were neglected in the previous studies. From many experimental results, Yuasa et al suggested that diffusion-limited combustion is dominant in the gas-phase reactions of polymethylmethacrylate (PMMA) with gaseous oxygen (GOX) in laboratory-scale hybrid rocket engines (6) . In this case, the mass flux exponent is slightly less than 0.8 (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%